PERAN SOSIAL PEREMPUAN DAYAK DI TIGA CERITA PENDEK KORRIE LAYUN RAMPAN - Aquari Mustikawati (Kantor Bahasa Kalimantan Timur, 2018)
This study describes the social role of Dayak women, both in the domestic and public spaces in three Korrie Layun Rampan short stories, namely